Electric distribution systems - Sallam , A. A. [ (Abdelhay A.)]; Malik, Om P. (IEEE Press series on power engineering, 2011)
"A comprehensive treatment of electric distribution systems is given in the book. Although a few books that cover specific topics in more depth are available, there is hardly any book that deals with the key topics of interest to distribution system engineers. It introduces these topics from two points of view: 1- The practical point of view by providing practical examples and the problems which can be met. 2- The academic point of view where the analysis and various techniques used for distribution system planning are explained. Therefore, the major outstanding feature of this book is a combination of practical and academic explanation of its contents. Another outstanding feature is a collection of the traditional and recent topics of distribution systems in one book"-- Provided by publisher